Foot plantar pressure monitoring with CYTOP bragg gratings sensing system - Vilarinho, Débora; Theodosiou, Antreas; Domingues, Maria Fátima F.; Antunes, Paulo; Kalli, Kyriacos; André, Paulo; Marques, Carlos Alberto F. (My University, 2018)
In this paper, a polymer optical fiber (POF) sensing solution to monitor the pressure induced in the foot plantar surface is investigated. The paper shows the design and implementation of a platform with an array of 5 polymer optical fiber Bragg gratings (POFBGs) placed in key points to monitor the pressure on the foot surface during gait cycles and the body center mass displacements. The results showed a great response compared with solutions using silica optical fibers. A much high sensitivity and repeatability were achieved using the CYTOP fiber as well as proving that the advantages of POF is a viable and useful solution for this type of application for a future implementation of an integrated “in-shoe” CYTOP POFBGs sensor network.
Keywords: Bragg Gratings; CYTOP; Gait Plantar Pressure; Physical Rehabilitation; Polymer Optical Fiber Sensors